Ideas and Opportunities for Entrepreneurship through the Value Chains - Libera, María Eugenia; Belmonte, Juan (Ingeniería Solidaria, 2015)
This research article is a product of the Strategic Plan of Buenos Aires (Plan Estratégico de Buenos Aires, pepba 2020), which consists of a working proposal with local businessmen and entrepreneurs so that, based on business ideas and opportunities detected in the value chains of strategic productive sectors, ideas for projects can be formulated and presented to fill those technological demands and needs. This article describes one such project: “unidea Cycle: Ideas and Opportunities for Entrepreneurship”. The objective of the project was to get the participants (entrepreneurs and young businessmen) to formulate projects that would help to channel demands that signify valuable business opportunities. The methodology consisted in involving businessmen from diverse productive sectors of the city, who presented the demands and needs observed in their companies, while specialists in the study and analysis of the local productive sphere described the characteristics of the value chains. The most representative result was that the participating businessmen and entrepreneurs are expressing interest in strengthening a way of creating a space focused on innovation.